Characterization of the influence of physical rehabilitation means and special physical exercises of archery on the sports performance of Paralympic athletes - Mahlovanyy, A.; Grygus, I.; Kunynets, O.; Duliba, S.; Strelbytskyi, L.; Ivanochko, O.; Homyshyn, V. (Rehabilitation & Recreation, 2023)
Determining the effect of an individually selected complex of special physical exercises in archery and physical rehabilitation means on the functional state of the cardiovascular, neuromuscular, and sensory systems and sports achievements of Paralympic athletes.